Lesotho : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues paper highlights that Lesotho's overall economic situation deteriorated significantly in 1998/99 after registering a slowdown in 1997/98. The economy had witnessed high annual average growth rates of more than 6 percent in the decade ended 1996/97. The strong growth was spurred largely by the construction of the Lesotho Highlands Water Project and the rapid expansion of the export and manufacturing sector. Real GDP growth decelerated sharply from 9.7 percent in 1996/97 to 4.1 percent in 1997/98 and then declined by 5.4 percent in 1998/99.